2007
DOI: 10.1007/s10464-007-9112-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive youth development programs on school, family, and community systems

Abstract: A review of efforts at social system change in 526 universal competence-promotion outcome studies indicated that 64% of the interventions attempted some type of microsystemic or mesosystemic change involving schools, families, or community-based organizations in an attempt to foster developmental competencies in children and adolescents. Only 24% of the reports provided quantitative data on the change that occurred in targeted systems. However, studies containing the necessary information produced several mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(112 citation statements)
references
References 165 publications
1
104
0
4
Order By: Relevance
“…Finally, in the community, in study 1, along with the meta-analysis developed by Durlak and colleagues [39], based on the impacts of PYD programs, the Dream Teens also argue that changes in their life contexts are necessary, revealing that they believe that the changes take a long time to happen, but that they left the Dream Teens brand, adding in study 2 that their work had an impact and will have repercussions in the future. With impacts on the future of the community, we can believe that the development of skills, knowledge, civic engagement, empowerment, selfconcept promotion [40] and feeling of respect and effectiveness [41], also contribute to a more positive development of young people participating in YPAR programs.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, in the community, in study 1, along with the meta-analysis developed by Durlak and colleagues [39], based on the impacts of PYD programs, the Dream Teens also argue that changes in their life contexts are necessary, revealing that they believe that the changes take a long time to happen, but that they left the Dream Teens brand, adding in study 2 that their work had an impact and will have repercussions in the future. With impacts on the future of the community, we can believe that the development of skills, knowledge, civic engagement, empowerment, selfconcept promotion [40] and feeling of respect and effectiveness [41], also contribute to a more positive development of young people participating in YPAR programs.…”
Section: Discussionmentioning
confidence: 96%
“…The approach uses a typical systematic review methodology but focuses on locating, evaluating and synthesizing published 'review-level' evidence (narrative reviews, systematic reviews and meta-analyses) and then extracts information on specific studies that may be Thirty-three systematic reviews were screened, of which nine were meta-analyses that met criteria for inclusion in the evidence map. As shown in Table 1, eight publications 13,[22][23][24][25][26][27][28] focused on outcomes of individuals participating in programmes: two reviews specifically examined mentoring programmes, two examined OST programmes and four examined health promotion, social competence and/or self-esteem (or self-concept ). A further review 29 examined the effects of development programmes from the perspective of the social systems involved (family, school, community).…”
Section: Evidence-mapping: Is Developmental Mentoring or Coaching Effmentioning
confidence: 99%
“…Supportive relationships help create a sense of appropriate boundaries and expectations while enhancing feelings of personal safety and development of a positive identity. Programs and activities that support social skill acquisition and relationship building can result in improvements in both academic achievement and self-perception (Durlak et al 2007). Hensley et al (2007) found that with increased involvement in 4-H, a youth's sense of belonging increased.…”
Section: Guiding Framework and Principlesmentioning
confidence: 99%